Let us equate the f(x) equal to zero,to find all the zeros of the given polynomial, hence, f(x) = 0:

x^3-27 = 0

We can use the formula below to factor the left-hand side.

a^3 - b^3 = (a - b)(a^2 + ab + b^2)

So, x^3 - 3^3 =...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Let us equate the f(x) equal to zero,to find all the zeros of the given polynomial, hence, f(x) = 0:

x^3-27 = 0

We can use the formula below to factor the left-hand side.

a^3 - b^3 = (a - b)(a^2 + ab + b^2)

So, x^3 - 3^3 = (x - 3)(x^2 + 3x +9) <---this is the **factored form of the polynomial**

Then, we equate each factor to zero:

x - 3 = 0 and x^2 + 3x + 9 = 0

For x - 3 = 0, we add 3 on both sides.

x - 3 + 3 = 0 + 3 ===> ** x = 3 one of the zeros**.

We use Quadratic formula for the x^2 + 3x + 9 = 0.

a = 1, b = 3 and c = 9.

So, x = [- 3 +/- sqrt((3)^2 - 4(1)(9))]/2(1)

===> x = [-3 +/- sqrt(9 - 36)]/2

===> x = [-3 +/-sqrt(-27)]/2

===> x =[ -3 +/- sqrt(9)*sqrt(3)*sqrt(-1)]/2

===> x = [-3 +/- 3i sqrt(3)]/2

or **other zeros are x = -3/2 + 3i sqrt(3)/2**

** x = -3/2 - 3i sqrt(3)/2**.